(untitled) (Revista de Ciências Agroveterinárias, 2022)
The type of operation of the seed drill metering mechanism and the operating speed are determinant in the crop’s productivity. Thus, the objective was to evaluate the longitudinal distribution of maize seeds with different seed metering mechanisms at different displacement speeds. The study was carried out at the Experimental Farm of Agricultural Sciences - FAECA of the Federal University of Grande Dourados (UFGD), in the municipality of Dourados, Mato Grosso do Sul (MS). The experimental design used was completely randomized in a 2 x 4 factorial scheme, with two seed dosers (pneumatic and mechanical) and four sowing displacement speeds (5, 7, 8 and 10 km-1). The longitudinal distribution of seeds was evaluated by checking the spacing between acceptable, flawed and multiple seedlings. The data were submitted to analysis of variance and the means were compared by the Tukey test at 5%. There was no significant difference up to the speed of 8 km h-1 for the mechanical feeder in the analysis of the performance of each mechanism within the different speeds. However, the pneumatic feeder achieved superior performance for faulty and double spacing. In general, for both metering mechanisms, the increase in sowing speed increased the number of faulty and double spacings. Therefore, the pneumatic metering mechanism showed a better response in the number of acceptable spaces with increasing speed.